Cerebrospinal fluid tau protein as a biochemical marker for Alzheimer's disease: a community based follow up study. Issue 3 (1st March 1998) - Andreasen, N; Vanmechelen, E; Van de Voorde, A; Davidsson, P; Hesse, C; Tarvonen, S; Räihä, I; Sourander, L; Winblad, B; Blennow, K
Abstract : OBJECTIVES: Biochemical markers for Alzheimer's disease would be of great value, especially to help in diagnosis early in the course of the disease. A pronounced increase in CSF tau protein (CSF-tau) is found in most patients with Alzheimer's disease. However, the specificity has to be further studied, as an increase in CSF-tau has also been found in other dementias, especially in vascular dementia. As most previous CSF studies have been based on selected inpatients, it was considered of special interest to examine the diagnostic potential of CSF-tau in a community population based sample of consecutive patients with dementia. Such patient material has been examined at the Piteå River Valley Hospital in Northern Sweden since 1986, and includes all those with memory disturbances in the community. The aim was also to study if an increase in CSF-tau is found early in the disease process, and whether CSF-tau changes during the progression of disease. METHODS: Participants: Community population based sample of 75 demented patients (43 with Alzheimer's disease, 21 with vascular dementia, and 11 with mixed Alzheimer's disease/vascular dementia), 18 healthy subjects, and 18 neurological controls. A follow up investigation (including analysis of a new CSF sample) was performed in all patients after about one year. MAIN OUTCOME MEASURES: Concentrations of total (both normal tau and PHF-tau) tau in CSF, clinical measures (duration and severity of dementia), and apoE polymorphism. RESULTS: CSF-tau was markedly increased in Alzheimer's disease, 41/43 (95%) patients had values above the cut off level (mean+2 SD) in controls (306 pg/ml). High CSF-tau concentrations were also found in most patients with vascular dementia, preferentially in patients with vascular dementia without progressive leukoaraiosis on CT, whereas patients with vascular dementia with progressive leukoaraiosis had normal CSF-tau. Concentrations of CSF-tau were stable at one year follow up in both patients with Alzheimer's disease and patients with vascular dementia, and there was no correlation between CSF-tau and either duration or severity of dementia. CONCLUSIONS: The findings confirm the high sensitivity of CSF-tau for the diagnosis of Alzheimer's disease, but high CSF-tau was also found in vascular dementia, resulting in a lower specificity. However, high CSF-tau is preferentially found in patients with vascular dementia without progressive leukoaraiosis, which may constitute a group with concomitant Alzheimer's disease pathology. High CSF-tau may be present during the whole course of the disease in Alzheimer's disease. Possibly, therefore, the same high CSF-tau concentrations may be present before the onset of clinical dementia. Follow up studies on such patients will tell whether analysis of CSF-tau is useful as a biochemical marker for early Alzheimer's disease.